A clinical guide for contraception - Speroff, Leon, 1935-; Darney, Philip D. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"The thoroughly updated Fifth Edition of this practical handbook is a current, reliable, and readable guide to the intelligent use of today's contraceptive options. The authors provide the essential information that clinicians and patients need to choose the best contraceptive method for the patient's age and medical, social, and personal characteristics. The book concisely covers all available drugs and devices. Each contraceptive method is covered in a single chapter that includes history of the contraceptive, method of action, pharmacology (when applicable), contraindications, and use. This edition includes new and updated information on new oral contraceptive pills, transdermal and vaginal delivery, post-pregnancy contraception, use of Essure for sterilization, and uses of contraceptives for non-contraceptive indications"--Provided by publisher.
(Publisher-supplied data) Contraception in the U.S.A. -- Oral Contaception -- Special Uses of Oral Contraception EMERGENCY CONTRACEPTION THE PROGESTIN-ONLY MINIPILL -- Transdermal and Vaginal Contraception -- Implant Contraception -- Injectable Contraception -- Intrauterine Contraception -- Barrier Methods -- Natural Family Planning: Periodic Abstinence and Withdrawal -- The Postpartum Period, Breastfeeding and Contraception -- CHAPTER 11: Clinical Guidelines for Contraception at Different Ages: Early and Late -- Sterilization -- Induced Abortion and Post-Abortion Contraception -- Interpreting Epidemiologic Reports and Contraceptive Eligibility Criteria EPILOGUE.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Contraception; Electronic books